Health-Care Telematics in Germany Design and Application of a Security Analysis Method - Sunyaev, Ali (Gabler, 2011)
Health-care telematics in Germany have been a much discussed topic in recent years. Based on the methodological foundation of design-oriented artifact construction in Information Systems (IS) research, in particular method engineering, Ali Sunyaev develops a method for the organizational and technical analysis of security issues in health care using tools, methods, and processes in a structured and traceable way. He identifies security problems in the current concept of German health-care telematics and derives recommendations for future developments in the health-care sector.